The Effect of Activity Ratios to Company Profitability in the Trading, Services, and Investment Sectors - Magdalena M, Annaria; Marpaung, Bintang Sahala; Hasibuan, David HM (Journal of Accounting, Business and Finance Research, 2021)
Profitability is a ratio that can be used to determine a company’s ability to generate profits. Information related to profitability is used to assess a company’s success in achieving its set goals. Profitability can also determine how effectively and efficiently a company’s activities have been carried out. This information is essential for potential investors to determine whether or not to invest in a company. This research was conducted to obtain information related to company profitability through activity ratios. The results are expected to be helpful for companies in assessing profitability. The subjects used in this study are companies engaged in the trade, services, and investment sectors listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019. A purposive sampling method was used and a total sample of 126 companies from eight sub-sectors was obtained. The analysis showed that the effects of working capital turnover and inventory turnover do not significantly impact profitability. In contrast, cash turnover was found to have a substantial impact on company profitability. Simultaneously, this study shows that working capital turnover, cash turnover, and inventory turnover significantly affect profitability. It also indicates that, simultaneously, a firm’s profitability is influenced by the activity ratio.